Comprehensive technology study of radiation hard LGADs. Issue 1 (1st November 2022) - Gkougkousis, E - L; Garcia, L. Castillo; Grinstein, S.; Coco, V.
Abstract : Towards radiation tolerant sensors for pico-second timing, several dopants are explored. Using a common mask, CNM produced LGADs with boron, boron + carbon and gallium gain layers are studied, under neutron and proton irradiation. With fluences ranging from 10 14 to 6 × 10 15 neq /cm 2 on both particle species, results focus on acceptor removal, gain reduction via electrical characterization, timing performance and charge collection. An emphasis is placed on stability via dark rate and operating voltage studies.